The necessity of redefining the concept of media literacy in the era of captological tools - Šmakić, Katarina (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
Numerous definitions of the term media literacy aim at different areas of literacy in the media space, from its basic concept, i.e. the individual's ability to create media content and to understand it, up to the metalanguage of the media themselves and critical thinking of their content. Democratic societies have lost awareness of the importance of terms such as "manipulation" or "propaganda", these terms today sound archaic and as if they have no relation to current time, also we associate them with historical events and think that they have disappeared, but the real truth is that they have essentially changed their forms. Snuggled down in our stereo reality, relying on the protection provided by democratic procedures, we are living in an unreal world that is far from our reality, and our reality is pure capitalism that does not choose means when it comes to the fight for profit. Manipulation and propaganda have taken on a completely new form and a new tool that uses computer programs as a technology for persuasion, and the question is following: does the user's choice is his own conditioned by the media message or is the user psychologically changed so that his response would be the way the computer software wanted it to be? Understanding the importance of interactive technologies and their impact on the change of minds, attitudes and values of the audience, as well as their impact on changing behavior and reliability in predicting it, is nowadays more important than just thinking about the concrete definition of media literacy. The scientific field known as captology, the use of technology for persuasion, uses existing knowledge from social psychology, communication studies, marketing and other fields, combined with the development of new computer software in order to elicit predictable user responses. If we say that the user is manipulated by computer programs, we will not give a detailed description of this kind of user instruction, because manipulation is seduction and giving certain disinformation, influencing facts, while captology does it on a much higher level, influencing human instincts and the unconscious in humans, and it purposefully provokes the user's already suggested responses. Captology examine those computer programs whose intention is to contain algorithms that, based on data from other disciplines such as social psychology and marketing, will be incorporated into them, and that the intent of persuasion will be part of that product itself. Captology is focused on change of behavior or attitude due to human-computer interaction, rather than through computer-mediated communication. The behavioral techniques used today have been converted into algorithms that predict with great precision the outcomes of the user's actions, create the user's needs and trap him in the magic circle. The necessity of redefining the term media literacy is extremely important nowadays, raising awareness of the importance of captology and incorporating it into media literacy, as well as research in the field of practical application of captological tools today, requires the necessity of continuing research in this new scientific discipline.
Keywords: media literacy; captology; captological tools; marketing